2016
DOI: 10.1016/j.jpaa.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The acyclicity of the Frobenius functor for modules of finite flat dimension

Abstract: Abstract. Let R be a commutative Noetherian local ring of prime characteristic p and f : R−→R the Frobenius ring homomorphism. For e ≥ 1 let R (e) denote the ring R viewed as an R-module via f e . Results of Peskine, Szpiro, and Herzog state that for finitely generated modules M , M has finite projective dimension if and only if Tor R i (R (e) , M ) = 0 for all i > 0 and all (equivalently, infinitely many) e ≥ 1. We prove this statement holds for arbitrary modules using the theory of flat covers and minimal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We choose not to make use of this result in this paper, however.) In [15], the second author together with M. Webb proved the analogue of Peskine and Szpiro's result for modules of finite flat dimension; that is, if M has finite flat dimension then Tor R i ( e R, M ) = 0 for all positive integers i and e. Further, it was shown that that the analogue of Herzog's result holds for arbitrary modules as well. Subsequently, Dailey, Iyengar and the second author [6] showed that if Tor R i ( e R, M ) = 0 for dim R + 1 consecutive positive values of i and infinitely many e, then M has finite flat dimension.…”
Section: Introductionmentioning
confidence: 93%
“…We choose not to make use of this result in this paper, however.) In [15], the second author together with M. Webb proved the analogue of Peskine and Szpiro's result for modules of finite flat dimension; that is, if M has finite flat dimension then Tor R i ( e R, M ) = 0 for all positive integers i and e. Further, it was shown that that the analogue of Herzog's result holds for arbitrary modules as well. Subsequently, Dailey, Iyengar and the second author [6] showed that if Tor R i ( e R, M ) = 0 for dim R + 1 consecutive positive values of i and infinitely many e, then M has finite flat dimension.…”
Section: Introductionmentioning
confidence: 93%
“…We remark that part (a) in the case M = R and L a finitely generated R-module is a classic result of Peskine-Szpiro [20,Théorèm 1.7]. This was later generalized to the case L is an arbitrary module in [19,Theorem 1.1], and to the case L is an arbitrary complex in [8, Theorem 1.1]. Part (b) was proved in [20,Théorèm 4.15] in the case M = R and L a finitely generated module, and in [19,Corollary 3.5] in the case M = R and L an arbitrary module.…”
Section: (A) If There Exists An Integer T Inf H(m ) + Sup H(l) Such T...mentioning
confidence: 77%
“…This was later generalized to the case L is an arbitrary module in [19,Theorem 1.1], and to the case L is an arbitrary complex in [8, Theorem 1.1]. Part (b) was proved in [20,Théorèm 4.15] in the case M = R and L a finitely generated module, and in [19,Corollary 3.5] in the case M = R and L an arbitrary module. Before stating the next corollary, we set some terminology and notation.…”
Section: (A) If There Exists An Integer T Inf H(m ) + Sup H(l) Such Tmentioning
confidence: 99%
“…Peskine and Szpiro [15] proved that (1)⇒(2), Herzog [10] proved that (3)⇒(1), and Koh and Lee [11] proved that (4)⇒ (1). Recently, the third author and M. Webb [14,Theorem 4.2] proved the equivalence of conditions (1), (2), and (3) for all R-modules, even infinitely generated ones. In their work, the argument for (3)⇒( 1) is quite technical and heavily dependent on results of Enochs and Xu [8] concerning flat cotorsion modules and minimal flat resolutions.…”
Section: Introductionmentioning
confidence: 99%